PENGUJIAN KECURANGAN LAPORAN KEUANGAN MENGGUNAKAN FRAUD HEXAGON MODEL (Media Riset Akuntansi, 2022)
The purpose of this study is to analyze fraudulent financial statements using fraud hexagon theory which consists of six elements are stimulus, capability, collusion, opportunity, rationalization, and ego. These elements are measured with financial stability, ineffective monitoring, change of auditor, change of directors, Frequent Number of CEO’S Pictures, and state-owned enterprises. The existence of mixed results and the phenomena regarding fraudulent financial statements, as well as the limited research using the fraud hexagon theory specifically in Indonesia, prompted this research to be carried out by investigating the factors that influence financial statement fraud. The population of this research is the manufacture sector companies listed on the Indonesia Stock Exchange (BEI) in 2016-2020. The sampling technique used a purposive sampling method. Based on these methods a sample size of 255 is obtained. The data analysis method uses logistic regression analysis. The results showed that the variables of financial stability, ineffective monitoring, change of directors, and frequent number of CEO’S pictures had no effect on fraudulent financial statements. Meanwhile, the financial stability and state-owned enterprise variable has a positive effect on fraudulent financial statements.